Konflikty interesów w firmach inwestycyjnych - Lewandowski, Mateusz (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The author of the article conducts an analysis of the conflicts of interest in investment companies as a fundamental and pervasive issue of the financial system. In following sections author analyze the current situation regarding to the significance of conflicts of interest, causes of conflict of interest on a capital markets and crucial legal regulations that prevents this problems or alleviates their impact. Additionally, the author points out the key elements of internal policies and procedures of investment firms that ensure control over providing appropriate advices to their clients
Keywords: firma inwestycyjna; konflikt interesów; giełda